2019
DOI: 10.1152/ajpendo.00540.2018
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide 26RFa (QRFP) is a key regulator of glucose homeostasis and its activity is markedly altered in obese/hyperglycemic mice

Abstract: Recent studies have shown that the hypothalamic neuropeptide 26RFa regulates glucose homeostasis by acting as an incretin and increasing insulin sensitivity. In this study, we further characterized the role of the 26RFa/GPR103 peptidergic system in the global regulation of glucose homeostasis using a 26RFa receptor antagonist and also assessed whether a dysfunction of the 26RFa/GPR103 system occurs in obese hyperglycemic mice. First, we demonstrate that administration of the GPR103 antagonist reduces the globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 33 publications
4
27
0
Order By: Relevance
“…Altogether, these findings reveal that depletion of 26RFa induces an alteration of glucose homeostasis that is due to a defect in insulin secretion but not in insulin sensitivity. Consistent with this finding, we have previously shown that 26RFa stimulates insulin secretion by the pancreatic β cells (24) and that administration of a 26RFa receptor antagonist alters the anti-hyperglycemic response of the organism to a glucose challenge (28). Collectively, these data confirm that 26RFa is an important regulator of glucose homeostasis.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Altogether, these findings reveal that depletion of 26RFa induces an alteration of glucose homeostasis that is due to a defect in insulin secretion but not in insulin sensitivity. Consistent with this finding, we have previously shown that 26RFa stimulates insulin secretion by the pancreatic β cells (24) and that administration of a 26RFa receptor antagonist alters the anti-hyperglycemic response of the organism to a glucose challenge (28). Collectively, these data confirm that 26RFa is an important regulator of glucose homeostasis.…”
Section: Discussionsupporting
confidence: 67%
“…Accumulated data obtained during the last decade have promoted the evidence that the neuropeptide 26RFa plays a key role in the control of feeding behaviour (10, 13, 14) and the regulation of glucose homeostasis (24, 25, 27, 28). Supporting this notion, it has been recently shown that acute administration of a GPR103 (the 26RFa receptor) antagonist decreases food intake (30) and reduces the global glucose-induced incretin effect as well as the insulin sensitivity (28). However, chronic deficiency of 26RFa signalling on energy and glucose homeostasis remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we reported that an oral glucose challenge induces a massive secretion of 26RFa by the gut into the blood, strongly suggesting that this neuropeptide regulates glycemia by acting as an incretin 24. This incretin effect of 26RFa has been very recently confirmed by the observation that administration of a GPR103 antagonist reduces the global glucose-induced incretin effect, and also decreases insulin sensitivity 28…”
Section: Introductionmentioning
confidence: 77%
“…Total RNA from livers of mice was isolated as previously described 28. Relative expression of glucose 6 phosphatase (G6PC), glucokinase (GCK) and phosphoenolpyruvate carboxykinase 1 (PCK1) genes was quantified by real-time PCR with appropriate primers (table 1).…”
Section: Methodsmentioning
confidence: 99%